PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DAN MOTIVASI TERHADAP HASIL BELAJAR SISWA SMP KRISTEN 4 TIKALA MANADO - Mendrofa, Jeffryman; Tamboto, Henry; Oroh, Silvana (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the effect of the use of learning media and motivation together on the learning outcomes of students of SMP Kristen 4 Tikala Manado. The research method used is the survey method, which is sourced from data and information mainly obtained from respondents as research samples using questionnaires or surveys as data collection instruments. The population in this study were students in grades VII, VIII and IX of SMP Kristen 4 Tikala Manado totaling 67 students. The sampling technique used was random sampling with a level of 5% so that a sample of 40 students was obtained. The results of the study showed that the use of Learning Media and Motivation had a significant effect on Student Learning Outcomes at SMP Kristen 4 Tikala Manado. Keywords: Learning Media, Motivation, Learning Outcomes